2020
DOI: 10.1029/2019gl086738
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Scattering of 90° Pitch Angle Electrons in the Outer Radiation Belt by Large‐Amplitude EMIC Waves

Abstract: Electromagnetic ion cyclotron (EMIC) waves can cause relativistic electron scattering and atmospheric precipitation, primarily via cyclotron resonant interactions in the Earth's radiation belts. However, the conventional quasilinear resonance theory suggests that the cyclotron resonance condition is not satisfied for 90° pitch angle (PA) electrons, which constitute the majority of electrons in the outer radiation belt, such that scattering mainly affects low‐PA electrons. In contrast to this theory, using test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 75 publications
0
16
0
1
Order By: Relevance
“…With the increasing observations of intense whistler mode waves (Agapitov et al, 2018; Kellogg et al, 2011; Zhang et al, 2018, 2019), the roles of nonlinear effects on radiation belt electrons dynamics get more and more attention. Many previous studies focused on the coherent nonlinear effects such as phase‐trapping and phase‐bunching on electron acceleration and precipitation (Artemyev et al, 2014, 2016; Gan et al, 2020; Lee et al, 2020; Omura et al, 2015). Here, we investigate nonlinear effects caused by large amplitude but still incoherent waves and test the validation of KM nonlinear resonance broadening theory.…”
Section: Resultsmentioning
confidence: 99%
“…With the increasing observations of intense whistler mode waves (Agapitov et al, 2018; Kellogg et al, 2011; Zhang et al, 2018, 2019), the roles of nonlinear effects on radiation belt electrons dynamics get more and more attention. Many previous studies focused on the coherent nonlinear effects such as phase‐trapping and phase‐bunching on electron acceleration and precipitation (Artemyev et al, 2014, 2016; Gan et al, 2020; Lee et al, 2020; Omura et al, 2015). Here, we investigate nonlinear effects caused by large amplitude but still incoherent waves and test the validation of KM nonlinear resonance broadening theory.…”
Section: Resultsmentioning
confidence: 99%
“…But for larger amplitudes the small oscillation may hit the bounce resonance and scatter the electron to off-equatorial motion. Lee et al (2020) performed test-particle simulations of 5-MeV electrons with an initial α eq = 90 • and different phase angles η integrating Eq. (6.47) in a dipolar B 0 (λ).…”
Section: Losses Caused By Emic Wavesmentioning
confidence: 99%
“…Additionally, Cao et al (2017) considered the bounce resonant scattering of near-equatorially mirroring electrons by H + -band EMIC waves (Roberts & Schulz, 1968) to more field-aligned pitch angles, where the cyclotron resonance can further scatter electrons into the loss cone. Most recently, D. Lee et al (2020) demonstrated that even electrons with a pitch angle of exactly 90° can be directly scattered by large-amplitude EMIC waves, which can eventually result in cyclotron resonant interactions leading to significant pitch angle changes. This process can take place without Landau or bounce resonance.…”
Section: Higher Pitch Angle Electronsmentioning
confidence: 99%
“…The EMIC wave‐electron interaction has also been examined via the nonlinear test particle approach (Albert & Bortnik, 2009; Lee et al., 2020, 2018; Lemons et al., 2009; Liu et al., 2012, 2010; Zhu et al., 2020), and the validity of the quasilinear diffusion theory has been examined with test particle simulations (Fu, Ni, Tao, et al., 2019; Su et al, 2012, 2013). Other aspects of the EMIC wave‐electron interaction that have been examined previously include oblique wave effects on relativistic electron scattering (Lee et al., 2018, 2020; G. Wang et al., 2017), precipitation by EMIC rising tone emission (Grach & Demekhov, 2020; Kubota et al., 2015; Kubota & Omura, 2016; Omura & Zhao, 2012, 2013), and nonresonant scattering (Chen et al., 2016). The typical electron resonance energy with EMIC waves is ∼MeV (Lorentzen et al., 2000), but lower resonance energy may be possible (Capannolo et al., 2018; Denton et al., 2019; Ukhorskiy et al., 2010; X. Zhang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation